A STUDY ON PROBLEMS AND PROSPECTS OF INTELLECTUAL PROPERTY RIGHTS IN INDIANPHARMACEUTICAL INDUSTRY - MG, LOGANATHAN (International Journal of Psychosocial Rehabilitation, 2019)
Ideas, innovations, and creative expressions based on which the public is ready to confer the status of property have been classified as intellectual property rights (IPR). IPR give the inventors or developers of a property certain exclusive rights in order for them to profit commercially from their creative work or reputation. Intellectual property protection comes in many forms, including patents, copyright, trademarks, and so on. A patent is granted to an invention that meets the requirements of worldwide novelty, non-obviousness, and industrial applicability. IPR is required for better invention or creativity identification, planning, marketing, rendering, and therefore protection. Depending on its field of expertise, each industry should have its own IPR rules, management style, strategies, and so on. In the approaching period, the pharmaceutical industry’s expanding IPR strategy will require a greater focus and approach. The pharmaceutical sector in India is expanding at a quicker pace. Indian pharma companies, on the other hand, are looking for worldwide commercial prospects like as export, contract research, and clinical trials. Intellectual Property Rights have become more important to many Indian businesses. The amount of money spent on research and development is likewise increasing. From their initial investment to strengthen their R&D to obtaining patent and other IP protection for their new breakthroughs, Indian pharmaceutical businesses confront numerous hurdles. Many legal formalities must be completed for drug discovery, paperwork, and clinical trials, among other things. The key issues confronting Indian pharmaceutical companies include the high cost of investment, the expiration of patented pharmaceuticals, the absence of clinical studies, the increased legal formalities, and the difficulties in getting IP protection.This research focused on both the issues that companies face as well as the opportunity that IPR provides for Indian pharmaceutical companies. The prevalent challenges related with IPR, particularly in relation to Indian pharmaceutical companies, provided a wider potential for this research. It is unavoidable that Indian pharmaceutical businesses will wish to safeguard their innovation through patents when they begin to invest more heavily in R&D and produce their own compounds that can be patented. As a result, the Indian government should promote and safeguard multinational company patents as well. Patents and other kinds of intellectual property (IP) rights are critical for industry and research and development. Businesses, particularly pharmaceutical companies, are unable to invest in R&D or produce new, creative treatments without robust protections.